Daylight Dynamics: A Preliminary Analysis of Radiation and Illuminance in Future Climate Scenarios - Chaves, Larissa; Carvalho Ayres Torres, Mauricio; Godoy Daltrozo , Jenifer; Tschiedel Martau, Betina (ENCONTRO NACIONAL DE CONFORTO NO AMBIENTE CONSTRUÍDO, 2025)
Abstract Accelerated urbanization and climate change have significantly impacted the availability and dynamics of daylight, particularly in densely built urban areas, influencing thermal conditions, energy efficiency, and human well-being. These impacts are directly related to variations in direct and diffuse solar radiation, illuminance levels, and surface temperatures, which influence how daylight interacts with the built environment and urban planning. Based on this, this study investigated these factors in a simulated urban model using Rhinoceros 3D, Grasshopper, and Ladybug Tools, aiming to understand their changes in future climate scenarios. Simulations were conducted for current and future (2080) climate scenarios in an urban block in Porto Alegre, Brazil, a city with a subtropical climate. The results indicate substantial increases in direct radiation and illuminance, with variations in exposure depending on the orientation of buildings. The conclusions highlight the importance of integrating daylight into urban planning to promote resilient and healthy environments, reinforcing the need for adaptive design strategies.